Do Early-Life Social, Behavioral, and Health Exposures Increase Later-Life Arthritis Incidence?. (August 2022) - Kemp, Blakelee R.; Ferraro, Kenneth F.; Morton, Patricia M.; Thomas, Patricia A.; Mustillo, Sarah A.; Crimmins, Eileen M.
Objectives: This study investigates direct and indirect influences of childhood social, behavioral, and health exposures on later-life osteoarthritis and rheumatoid arthritis development. Methods: Drawing from cumulative inequality theory and six waves of the Health and Retirement Study (2004–2014), we estimate structural equation modeling-based discrete-time survival analysis of the association between six childhood exposure domains and both osteoarthritis and rheumatoid arthritis incidence for men ( n = 2720) and women ( n = 2974). Using the delta method to test for mediation, we examine indirect effects via selected health-related risks and resources. Results: Risky adolescent behavior is associated with rheumatoid arthritis incidence for women (h.O.R. = 1.883, 95% C.I. [1.016, 3.490]), whereas several types of childhood exposures are associated with later-life osteoarthritis development for both men and women. Experiencing two or more childhood socioeconomic disadvantages is indirectly associated with osteoarthritis (men: coef. = 0.024, 95% C.I. [0.003, 0.045]; women: coef. = 0.111, 95% C.I. [0.071, 0.150]) and rheumatoid arthritis (men: coef. = 0.037, 95% C.I. [0.000, 0.074]; women: coef. = 0.097, 95% C.I. [0.035, 0.159]) development through adult body mass index. Discussion: Findings highlight the importance of childhood contexts in understanding the development of later-life osteoarthritis and rheumatoid arthritis.